Direct observation of phase transitions between delta- and alpha-phase FAPbI 3 via defocused Raman spectroscopy - Sturdza, BK; Gallant, BM; Holzhey, P; Duijnstee, EA; von der Leyen, MW; Sansom, HC; Snaith, HJ; Riede, MK; Nicholas, RJ (Royal Society of Chemistry, 2024)
The ability to characterise perovskite phases non-destructively is key on the route to ensuring their long-term stability in operando. Raman spectroscopy holds the promise to play an important role in this task. Among all perovskites, formamidinium lead iodide (FAPbI3) has emerged as one of the most promising candidates for single-junction photovoltaic cells. However, Raman spectroscopy of FAPbI3 remains challenging as is evidenced by conflicting reports in the literature. Here, we demonstrate that due to the vulnerability of FAPbI3 to laser-induced degradation, the detected Raman spectrum depends strongly on the experimental conditions. This can lead to conflicting results and is revealed as the origin of discrepancies in the literature. We overcome this issue by deploying defocused Raman spectroscopy, preventing laser-induced damage to the sample and simultaneously improving the signal-to-noise ratio, allowing us to furthermore resolve much weaker Raman modes than was previously possible. We offer step-by-step instructions on how to apply this technique to a given spectrometer. Non-destructive characterisation of the FAPbI3 phases further enables us to quantify the phase stability of pristine FAPbI3 crystals and FAPbI3 grown with the high-performance additive methylenediammonium chloride (MDACl2). This shows that the neat crystals fully degrade within two weeks, whereas in samples grown with the additive only about 2% of the crystal bulk is in the δ-phase after 400 days. This establishes defocused Raman spectroscopy as a powerful tool for the characterisation of FAPbI3 and other perovskite materials.